Engaged Play: Insurgent Possibilities in Times of Climate Emergency - Vendramini-Zanella , Daniela Aparecida; Estefogo, Francisco; Fuga, Valdite Pereira; Carrijo, Viviane Letícia Silva; Modesto-Sarra, Luciana Kool (The ESPecialist, 2025)
This article discusses Engaged Play as a transformative pedagogical practice within an intercultural school context, particularly in addressing water-related issues resulting from environmental imbalance. The proposal is anchored in the work of the group Researchers in Intercultural Actions (R.I.A.) during the Ecorama event held at Brooklyn New School (BNS) in New York, USA. The study analyzes how children, educators, and families were invited to critically reflect on water-related disasters, such as the floods that occurred in Rio Grande do Sul in May 2024. The activities are grounded in Vygotsky’s socio-historical-cultural perspective, as well as in intercultural epistemology and Engaged Multiliteracies. The results show that Engaged Play has the potential to promote social transformation, ethical engagement, and intercultural dialogue. The study also highlights the importance of collaboration between schools and universities to expand this approach and proposes directions for future research that deepen its impact and potential to inform school activities in diverse educational contexts.